Evaluation of effect of tuned liquid dampers and modified tuned liquid dampers on seismic response of steel moment resisting frames - Nader Hoveidae (Iranian Society of Structrual Engineering (ISSE), 2021)
Severe damages of structures during large earthquakes and the loss of national wealth has made it extremely important to reduce the vibrations of structures against wind and earthquake. One of the efficient ways to reduce these vibrations, is to use the tuned liquid damper (TLD). The tuned liquid damper is the passive control system of the structure, which is made up of several fluid-containing reservoirs placed at the highest point of the building. The vibrational energy entangled to the structure is dissipated due to the turbulence of the liquid inside tanks. This system is used to control the vibrations of structures that have one or more degrees of freedom. In this research, the modified passive structural control system is used for checking the effects of the volumetric tuned liquid damper out and its results are compared with the traditional one. In this regard, three buildings including 4, 8 and 20 story moment resisting frames with three different mass ratio of 1, 2 and 3 percent were designed in ETABS software. Finally, Pushover analysis and nonlinear time history analyses were conducted in OPENSEES software results of the analysis show that the use of these dampers greatly reduces the peak drifts and peak residual drift demands of structures. On the other hand, the ability of the modified tuned liquid damper (MTLD) to reduce the residual and inter-story drift is greater in comparison to TLD.